ANALISIS PENGARUH BOOK-TAX CONFORMITY TERHADAP PERSISTENSI LABA - Feidy, Cathlin; Madya, Synthia (Balance : Jurnal Akuntansi, Auditing dan Keuangan, 2017)
The difference between accounting earnings and taxable income in the research have been debated extensively. The difference raises two different perspectives, proponents of increased book-tax conformity argue that tax compliance will increase and earnings quality will improve. Opponents argue  that earnings quality will decline. The objective of this research is to analyze and to obtain empirical evidence about the effect of book-tax conformity on earnings persistence in manufacturing companies which is listed on Indonesian Stock Exchange (IDX) in 2010-2014. This research’s data is obtained from company’s audited financial statements that have been published. This research has a total of 340 samples. Hypothesis examination in this research is done by using linear regression analysis method. The hypothesis examination uses loss and earnings variance as control variables. Result of the hypothesis examination shows that book-tax conformity effects the earnings persistence, consistent with the research’s hypothesis, and the effect is positive. It means that higher book-tax conformity may result in higher earnings persistence. The result also shows that loss is less persistence and earnings variance is not effect the earnings persistence. Keywords: book-tax conformity, earnings persistence, loss, earnings variance